Analysis of System Degrees of Tilts of Solar Panel for Energy Utilization Using Solar Test Simulator - Cholish; Ibnu Hajar; Sharfina Faza; Zumhari; Abdul Azis; Faisal Irsan P; Abdullah (International Journal of Research in Vocational Studies (IJRVOCAS), 2023)
The design of the Solar Panel Test Simulator by means of setting the solar panel placement stand so that the designed tool is able to provide a simulation of solar panel measurements based on actual conditions. The performance of the solar panels is shown through a monitor display placed on the design that will contain information about the solar panels as a whole. Limitations in placing the position of the solar panel will not provide a reference regarding measurement conditions based on the angle of incidence of the sun, so it is necessary to do further design regarding the position of the solar panel when the measurement is carried out. The development carried out in the design of this tool is in the form of setting the solar panel mount in the form of a solar panel mount tilt of 450, 900, 1350, and the distance of the halogen lamp 30cm as the energy source is measured. The measurement results are based on an average design temperature difference of 0.49% with a voltage of 1.55%.